Imajinasi matematis siswa field independent dan field dependent dalam menyelesaikan soal HOTS - Rizkiyanti, Eva; Sholihah, Ummu; Sutopo, Sutopo (UNIVERSITAS NEGERI MALANG, 2024)
AbstractImagination is the basis of figurative thinking that allows a person to solve problems without practical action. Mathematical imagination has nine indicators: exploration, intuition, novelty, sensitivity to productivity, elaboration, crystallization, transformation, and effectiveness. This study aims to 1) Analyze the Mathematical Imagination of field independent students in solving HOTS problems, 2) Analyze the Mathematical Imagination of field dependent students in solving HOTS problems. This research uses a qualitative approach by a type of case study research. The instruments used GEFT test, Mathematical Imagination test and interview. This study took 4 students consisting of 2 field independent students and 2 field dependent students. The results showed that the mathematical imagination of field independent students gave rise to nine indicators. While the mathematical imagination of field dependent students only raises five indicators, namely intuition, exploration, transformation, crystallization and sensitivity. Keywords: Mathematical imagination, Field Independent, Field Dependent, HOTS Problem